1987
DOI: 10.1038/ki.1987.140
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the development of experimental membranous nephropathy

Abstract: Heymann nephritis is a rat model of glomerulonephritis with morphologic manifestations of human membranous nephropathy. This model is generated by immunizing rats with Fx1A antigen. Passive Heymann's nephritis (PHN) can be produced by the administration of anti-Fx1A antibody (anti-Fx1A Ab) (with abnormal proteinuria appearing in 5 days). Studies were designed to examine the evolution of temporal changes in protein excretion, the glomerular ultrafiltration coefficient (LpA) and morphology of glomerular capillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In rats with experimental nephritis or 1-sided nephrectomy, glomerular hypertension appears without hypertension. 21,22,25,26 The glomerular pressure in our patients with normal to high-normal pressure may be higher than that in our patients with optimal pressure. We calculated the glomerular pressure in the patients of this study by the method used in our previous study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In rats with experimental nephritis or 1-sided nephrectomy, glomerular hypertension appears without hypertension. 21,22,25,26 The glomerular pressure in our patients with normal to high-normal pressure may be higher than that in our patients with optimal pressure. We calculated the glomerular pressure in the patients of this study by the method used in our previous study.…”
Section: Discussionmentioning
confidence: 67%
“…SSI was different among the groups. The median glomerulosclerosis score was different in the groups (optimal group, 33 [25th to 75th percentile, 3, 82]; normal to high-normal group, 125 [25,185]; and hypertensive group, 160 [106, 176] Figure 2a). The median score for tubulointerstitial damage was different among the groups (optimal group, 5 [0, 9]; normal to high-normal group, 10 [10,30]; and hypertensive group, 30 [20,40]; Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of subepithelial IgG and C3 in the GBM is one of the hallmarks of HN and human membranous nephropathy, and the importance of the early complement components in PHN is well established. Rats depleted of complement with cobra venom factor do not develop proteinuria in PHN (13,46,47), and Baker et al (48) showed that depletion of C6 with a mAb prevented proteinuria in PHN. However, the pathogenic role of the MAC complex has been questioned with the induction of both active HN (15) and PHN (49,50) in a C6-deficient PVG rat strain.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of C3 by anti-Fx1A Abs leads to formation of the membrane attack complex (C5b-9/MAC), which is thought to mediate sublytic injury to GEC, synthesis of abnormal glomerular basement membrane (GBM) matrix, and proteinuria (10,11). In passive HN (PHN), C3 depletion with cobra venom factor abrogates proteinuria, suggesting complement is the principal mediator of glomerular injury (12,13). Ab responses that block the function of the complement regulatory molecule Crry, the rodent analogue of human decay-accelerating factor and monocyte chemoattractant protein, are also necessary for the development of proteinuria in HN (14).…”
Section: Mmune Injury In Glomerulonephritis Is Categorized As Eithementioning
confidence: 99%
“…The formation of the C5b-9 in rat PHN has been shown to stimulate the production of arachidonic acid, prostaglandin F2a (PGF2a) and thromboxne A2 (TXA2) (14). The reduction of the RBF of rats with APHN is probably due to the increase in glomerular synthesis of prostanoids such as PGF2a and TXA2 that induce vasoconstriction (15,16). At the present time, TJ-8014, given as a single p.o.-dose of 4.0 g/kg, inhibited the de crease in the RBF by 57%.…”
Section: Discussionmentioning
confidence: 99%